La moda come motore economico: innovazione di processo e prodotto, nuove strategie commerciali, comportamento dei consumatori / Fashion as an economic engine: process and product innovation, commercial strategies, consumer behavior - Nigro, Giampiero (Datini Studies in Economic History, 2022)
The study of the textile sector has always been central to economic history: from reconstructions of the dynamic growth in the medieval wool industry, to the rise of silk and light and mixed fabrics in the modern era, to the driving role of cotton in the industrialisation process. Although the dynamics of textile manufacturing are closely linked to the transformations of fashion, economic history has long neglected its role as a factor in economic change, treating it primarily as a kind of exogenous catalyst. This book makes a decisive contribution to the understanding of a fundamental transformation, the consequences of which are projected into contemporary society, but which matured in pre-industrial times: the advent of fashion.